COMPOSITION AND ORIGIN OF FLUIDS ASSOCIATED WITH LODE GOLD DEPOSITS IN A MESOARCHEAN GREENSTONE BELT (WARRAWOONA SYNCLINE, PILBARA CRATON, WESTERN AUSTRALIA) USING SYNCHROTRON RADIATION X-RAY FLUORESCENCE - Thébaud N.; Philippot P.; Rey P.; Cauzid J. (My University, 2006)
Microthermometry and Raman spectroscopy techniques are routinely use to constrain ore-fluids δ18O and molar proportions of anhydrous gas species (CO2, CH4, N2). However, these methods remain imprecise concerning the ore-fluids composition and source. Synchrotron radiation X-ray fluorescence allows access to major and trace element concentrations (Cl, Br and K, Ca, Fe, Cu, Zn, As, Rb, Sr) of single fluid inclusion. In this paper, we present the results of the combination of these routine and newly developed techniques in order to document the fluids composition and source associated with a Mesoarchaean lode gold deposit (Warrawoona Syncline, Western Australia). Fluid inclusion analyses show that quartz veins preserved records of three fluid inclusion populations. Early fluids inclusions, related to quartz veins precipitation, are characterized by a moderate to high Br/Cl ratio relative to modern seawater, CO2 ± CH4 ± N2, low to moderate salinities and significant base metal (Fe, Cu, Zn) and metalloid (As) concentrations. Late fluid inclusions trapped in secondary aqueous fluid inclusions are divided into two populations with distinct compositions. The first population consists of moderately saline aqueous brines, with a Br/Cl ratio close to modern seawater and a low concentration of base metals and metalloids. The second population is a fluid of low to moderate salinity, with a low Br/Cl ratio relative to modern seawater and significant enrichment in Fe, Zn, Sr and Rb. These three fluid inclusion populations point to three contrasting sources: (1) a carbonic fluid of mixed metamorphic and magmatic origin associated with the gold-bearing quartz precipitation; (2) a secondary aqueous fluid with seawater affinity; and (3) a surface-derived secondary aqueous fluid modified through interaction with felsic lithologies, before being flushed into the syncline. Primary carbonic fluids present similar characteristics than those ascribed to Mesoarchaean lode gold deposits. This suggests similar mineralization processes for mid- and Mesoarchaean lode gold deposits despite contrasting fluid–rock interaction histories. However, in regard to the protracted history documented in the Warrawoona Syncline, we question the robustness of the epigenetic crustal continuum model, as ore-fluid characteristics equally support an epigenetic or a polyphased mineralization process.
Keywords: FLUID INCLUSION COMPOSITION; PILBARA; SYNCHROTRON; GOLD DEPOSIT; MESOARCHAEAN; Докембрий::Архей::Мезоархейская; Precambrian::Archean::Mesoarchean